Association between Physical Activity and Age among Children with Overweight and Obesity: Evidence from the 2016-2017 National Survey of Children's Health. (24th September 2020) - Li, Xun; Xiang, Shi-Ting; Dong, Jie; Zhong, Yan; Zhao, Sha; Xiao, Zhenghui; Li, Liping
Abstract : Physical activity participation in children declines with age. It is not clear yet whether the age-related trends vary by weight status. This study is aimed at investigating the association between physical activity participation and age among children with healthy weight, overweight, or obesity, using data from the 2016-2017 National Survey of Children's Health (NSCH). Physical activity participation was evaluated by days participated in physical activity for at least 60 minutes out of 7 days. Weight status was categorized from body mass index (BMI) percentiles. Data were analyzed on 33, 056 US children age 10-17 years. The percentages of been active 0 day out of 7 days in BMI5 th < 85 th (healthy weight), 85 th < 95 th (overweight), and ≥95th percentile (obese) groups were 8.9%, 11.5%, and 18.2%, respectively. Among all groups, been active 0 day out of 7 days was positively associated with age, while the strongest associations were observed in the BMI85 th < 95 th group (age 17 years vs. age 10 years: OR = 7.48, p < 0.0001 ). Older age was significantly associated with been active less than 4 days out of 7 days in the BMI5 th < 85 th and 85 th < 95 th groups, but those associations were attenuated in the BMI ≥ 95 th group. This study found that physical activity participation was inversely associated with age among children with healthy weight, overweight, or obese, and the association was strongest among children with overweight and weakest among children with obesity. Interventions aimed at promoting physical activity among children should take these patterns of association into account.